A study of modeling of flue gas patterns with number and shape variations of the catalytic converter filter - Ghofur, Abdul; Subagyo, Rachmat; Isworo, Hajar (Eastern-European Journal of Enterprise Technologies, 2018)
Exhaust gas in motorized vehicles is the main source of air pollution in the environment. Pollution of motor vehicle exhaust can be reduced by paying attention to the maintenance system, modern engine control concepts, fuel cleaning, and reduction of exhaust emissions. Catalytic converters are the most effective tool to fight pollutants in our environment because they reduce nearly 80 % of the harmful gases that result from incomplete combustion of the engine. To find out the flow phenomena that occur, a simulation of the pattern of exhaust gas flow is made with variations in the number and shape of the Catalytic converter filter. This research begins with the making of a Catalytic converter design which includes: filternotcut and filtercut dimensions. Then design the frame dimensions of the Catalytic converter with a variety of filters: 2, 3, 4 and 5 pieces and do the simulation. The simulation results show that the increase in speed percentage is caused by the exhaust gas flow passing through the small holes in the filter so that the gas pressure changes to an increase in speed. Installation of 2 filternotcut pieces is recommended because there is no vacuum area. The addition of the number of filters increases the vacuum area that occurs, this is related to the durability of the Catalytic converter. The simulation results suggest using the 3 most durable filtercut pieces compared to using filters: 2, 4 and 5 pieces. In filternotcut (3, 4 and 5 pieces), the random pressure distribution is caused by the nonuniform pressure. This nonuniform flow decreases the efficiency and durability of the Catalytic converter. Unlike the case with 3 filtercut pieces that have a more regular pressure distribution, are more solid and fused